Carbon footprint as a marker of environmental impact in patients included in a remote monitoring pacemaker programme. (14th October 2021) - Perez Diaz, P; Jimenez Diaz, J; Higuera Sobrino, F; Bastante Diaz, M C; Campos Perez De Madrid, E; Fernandez Trujillo, A; Cano Rosado, L; Bermejo Calvillo, N; Casas De Miguel, A M; ,
Abstract: Background: When patients fitted with pacemakers have to attend arrhythmia appointments, this often involves their caregivers having to take time off work, along with an increase in spending on transport and the amount of CO2 emissions into the atmosphere (carbon footprint). The remote monitoring of pacemakers implemented at our Arrhythmia Unit reduces the social, occupational, financial and environmental impact. Purpose: We describe the impact of remote monitoring of pacemaker implemented by our Arrhythmia Unit in our patient's live and the reduction in social, occupational and financial impact on these patients, and we quantify the decrease in CO2 emissions. Methods: Prospective observational study including 160 patients on the remote monitoring programme between 2016 and 2017. We handed a satisfaction survey to these patients after the face-to-face monitoring appointment, which analysed variables such as waiting time, attention and treatment received, need for accompaniment of a relative, method of travel and kilometres travelled, etc. Finally, we quantified the carbon footprint of each patient's journey and compared the level to the results if all the monitoring appointments had been in person. Results: Patients spent a median of 60±30 minutes in remote monitoring, with a distance travelled of 1.4±4.9 km. In face-to-face appointments, most patients were accompanied (85.6%) and arrived by private car (66.3%), with 54% of family members needing to take time off work. The median time spent was 150±120 minutes, and the distance travelled was 63±105 km. The carbon footprint emitted by individuals included in the remote monitoring programme was 138±114, with an estimated saving of 15±33 kg of CO2 (9.6%) per remote monitoring cycle (Figure 1). Conclusions: The remote monitoring pacemaker programme in the health district of our city has a very positive healthcare, social-occupational and environmental impact, which is manifested both from an objective point of view (greater independence, less time spent per appointment, less distance travelled, fewer healthcare transport needs, less workplace absenteeism by family members and approximately a 10% reduction in CO2 emissions per monitoring cycle) and a subjective point of view (lower impact of appointments on patients' lives and greater perception of satisfaction from the patients and their companions). Funding Acknowledgement: Type of funding sources: None.